Isolation and Characterisation of Dichelobacter Nodosus from Footrot Infected Sheep in Malaysia - Zakaria, Zunita (1998)

(untitled)
Twelve Dichelobacter nodosus were isolated from 12 sheep with footrot with lesion score 2. The isolates were studied and the results analysed. Diagnosis was done successfully by Gram-stain method while polymerase chain reaction (PCR) method with species specific primers, A and Ac were employed for species confirmation. All 12 isolates reacted positively in the peR method by producing a single product of approximately 780 basepairs. All isolates, although obtained from distant locations, were from serogroup B (10 isolates were B2 serotype, 2 isolates were B1 serotype). The E-test method was used to determine the minimum inhibition concentration (MIC) values of nine antimicrobial agents against all 12 isolates. Penicillin G proved to be the most effective antibiotic with MIC90% of 0.023 ug/ml. Two standard conventional methods, the elastase and gelatin gel tests, were used in assessing the virulence of the isolates. Generally, the isolates exhibited variation in the laboratory characteristics although they had been isolated from similar lesion score. Some of the isolates which appeared to have the capability of causing virulent footrot in-vitro, failed to show clinical signs of virulent form of footrot. This was probably due to the frequent topical regimen adhered to and result of the vaccination programme by the farm management. All isolates were found not to contain plasmid by standard plasmid extracting method. This indicates that the genes coding for virulence of the isolates were not plasmidmediated. Molecular typing of the isolates was successfully carried out by pulsed field gel electrophoresis (PFGE) analysis. Significant patterns were generated by three GC-rich enzymes (ApaI, SfiI and SmaI) discriminating the isolates into eight genome types. Isolates from the same flock were also shown to possess variation in their PFGE profiles. These results demonstrate the diversity of D. nodosus strains infecting sheep in Malaysia and also indicated that the isolates were from diverse sources.